Results and needs of training of trainers of NGO staff working in the earthquake zone after the devastating earthquake in Turkey on 6 February (Turkey Health Literacy Journal, 2024)
Earthquakes are natural disasters resulting from the sudden release of energy in the earth’s crust. These events affect not only the physical infrastructure but also the general health of the society. Earthquakes, as natural disasters, have far-reaching consequences on healthcare systems, affecting not only immediate medical needs but also the long-term well-being of communities. Along with the acute period of the earthquake, many non-governmental organisations have started to serve in the earthquake region until today. Especially in the field of health, in order to protect public health, many non-governmental organisations continue to work with the public authority in terms of both education and financial support to the earthquake victims. During the visits to the region, it was noteworthy that there were differences in the training and communication skills of the volunteer groups working in these organisations. In order to minimise these differences and to convey the correct information to the society with appropriate communication and training techniques, it was planned to train 30 people from NGO employees providing services in the earthquake region. Methods At the beginning of October 2023, the planned training was announced via e-mail to the managers of NGOs active in the earthquake region. From the first NGOs that applied, 3-5 participants were recruited and 30 people were completed. Results: According to the number of correct answers given by the participants, a statistically significant difference was found in the analysis made according to the total number of correct answers in the pretest and posttest (p<0.001). While 20 (69.0%) of the participants found the duration of the training appropriate, 8 (27.6%) stated that it was too short. When asked to rate the contribution of this training to their personal skills on a scale of one to ten, the participants gave an average answer of 8.10±1.68. When asked which of the topics covered in this training in the evaluation form would be most useful in your profession, 76% (22/29) stated communication skills, 68.9% stated WASH training, 65.5% (19/29) stated problem solving, 55.17% (16/29) stated all topics, and 34% stated primary health care. The content of the training should be reviewed and expanded, taking into consideration the feedback and expectations from the course participants. Efforts should be made to increase the participation of NGOs and stakeholders in the upcoming training sessions. The continuation of providing training and other support for public health improvement in the region is deemed necessary.